2016
DOI: 10.18632/oncotarget.14049
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of prostate cancer with FGF receptor and AKT kinase inhibitors

Abstract: Activation of the PI3K/AKT pathway occurs in the vast majority of advanced prostate cancers (PCas). Activation of fibroblast growth factor receptor (FGFR) signaling occurs in a wide variety of malignancies, including PCa. RNA-Seq of castration resistant PCa revealed expression of multiple FGFR signaling components compatible with FGFR signaling in all cases, with multiple FGF ligands expressed in 90% of cases. Immunohistochemistry confirmed FGFR signaling in the majority of xenografts and advanced PCas. AZD536… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…Examination of the smaller number of metastatic cases with mRNA revealed a similar pattern. As seen in Figure 7B , 16 of 19 metastatic cases had upregulation of one or more FGF ligands, with up to 13 ligands increased in some cases, similar to our previously reported finding in the metastatic cancers analyzed at Fred Hutchison Cancer Center [ 26 ]. PTEN loss was much more common in the metastatic cases, as is well known [ 34 ].…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Examination of the smaller number of metastatic cases with mRNA revealed a similar pattern. As seen in Figure 7B , 16 of 19 metastatic cases had upregulation of one or more FGF ligands, with up to 13 ligands increased in some cases, similar to our previously reported finding in the metastatic cancers analyzed at Fred Hutchison Cancer Center [ 26 ]. PTEN loss was much more common in the metastatic cases, as is well known [ 34 ].…”
Section: Resultssupporting
confidence: 87%
“…Previous studies by our group and others [ 21 , 22 , 25 27 , 29 , 31 ] individual ligands and receptors have shown multiple ligands and receptors are increased in PCa. Our recent collaborative bioinformatic study of metastatic prostate cancers based on RNA sequencing showed a pattern like our current study; almost ubiquitous but highly variable expression of FGF ligands and receptors in these cancers [ 26 ]. Given that PTEN is lost or AKT is activated by alternative mechanisms in the vast majority of advanced PCas [ 34 ], our current studies provide a reasonable explanation for these observations.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations